PRODUKSI BEBERAPA VARIETAS BAWANG MERAH TRUE SHALLOT SEED (TSS) TERHADAP PEMBERIAN BOKASHI - Reza Zulfahmi; Mustika Adzania Lestari; Hevia Purnama Sari; Desty Aulia Putrantri (AGRORADIX : Jurnal Ilmu Pertanian, 2023)
Shallots are included in the horticultural value-added products because of their high economic value. Shallots consumption continues to increase but has not been followed by an increase in its productivity. Shallot productivity can be increased by applying bokashi. This study aims to determine the production of several True Shallot Seed varieties to bokashi application. The research used a factorial randomized block design (RBD) consisting of two factors. The first factor is TSS varieties namely Sanren, Lokananta, Maserati and Tuk-tuk. The second factor is bokashi with a dose consisting of 0 kg m-2, 2.5 kg m-2, and 5 kg m-2. There were twelve treatments repeated three times. The observed characters were bulb length, bulb diameter, number of tillers, bulb fresh weight, bulb dry weight, bulb fresh weight per cluster, bulb dry weight per cluster. The results showed that Maserati and Sanren varieties had high production with bulb dry weight per cluster of 36.49 grams and 33.15 grams, respectively. The application of bokashi at a dose of 2.5 kg m-2 is more efficient than a dose of 5.0 kg m-2 because both can increase the bulb length, bulb diameter, bulb fresh weight, and bulb dry weight.